2015
DOI: 10.1002/joc.4506
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the upper ocean heat content in the equatorial Atlantic during boreal spring and the Indian monsoon rainfall during June–September

Abstract: ABSTRACT:Earlier studies have identified a teleconnection between the Atlantic zonal mode (AZM) and Indian summer monsoon rainfall (ISMR), both of which are active during the boreal summer (AZM: June-August; ISMR: June-September). It is known that El Niño-Southern Oscillation (ENSO)-like coupled dynamics are operational in the tropical Atlantic during the AZM events. Our goal here is to extend this process understanding to seek a predictive relation between the tropical Atlantic and the ISMR based on these kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 63 publications
6
27
0
Order By: Relevance
“…A cold (warm) phase of AZM is defined when the normalized AZM index is lower (greater) than 1 standard deviation. Prior to the analysis, the influence of ENSO is removed (details in supporting information Text S1) from all the variables following the methodology adopted in the previous studies (Pottapinjara et al, ; Sabeerali et al, ). The statistical significance of the correlation analysis is estimated using Pearsons test.…”
Section: Methodsmentioning
confidence: 99%
“…A cold (warm) phase of AZM is defined when the normalized AZM index is lower (greater) than 1 standard deviation. Prior to the analysis, the influence of ENSO is removed (details in supporting information Text S1) from all the variables following the methodology adopted in the previous studies (Pottapinjara et al, ; Sabeerali et al, ). The statistical significance of the correlation analysis is estimated using Pearsons test.…”
Section: Methodsmentioning
confidence: 99%
“…Chattopadhyay et al, 2015). Recently, also the tropical South Atlantic (TSA) and the Atlantic zonal mode have been identified as source for Indian monsoon variability and predictability (Kucharski et al, 2007(Kucharski et al, , 2008Losada et al, 2010;Barimalala et al, 2011;Pottapinjara et al, 2014Pottapinjara et al, , 2015. It should be noted that the TSA and Atlantic zonal mode are closely related (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The impact from other ocean basins is of secondary importance. On the other hand, the correct representation of these other teleconnections could provide improved predictability of the Indian monsoon, particularly in non-ENSO years (Pottapinjara et al, 2014(Pottapinjara et al, , 2015. The TSA-Indian monsoon teleconnection has also been identified as the leading mode in the coupled variability between the tropical Atlantic region and the Indian monsoon (Syed and Kucharski, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The last four decades of climate research have revealed the influence of the ocean-atmosphere coupled system variability within the tropical Atlantic basin on the observed climate conditions in the adjacent continental regions [1][2][3][4][5][6]. Recent studies have also shown that atmospheric perturbations generated in this region by the ocean-atmosphere coupled variability act as forcing conditions on the El Niño-Southern oscillation (ENSO) [7][8][9][10], Pacific meridional mode [11], North Atlantic oscillation (NAO) [10,12], and Indian monsoon [13,14]. Therefore, a more accurate understanding of the tropical Atlantic variability could improve climate prediction over the adjacent regions, benefiting their 2 of 16 populations, and, from a broader perspective, deepen our understanding of the interactions between the tropical Atlantic variability and diverse large-scale phenomena.…”
Section: Introductionmentioning
confidence: 99%